2012
DOI: 10.2147/ijgm.s38020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consuming alcohol mixed with energy drinks versus consuming alcohol only on overall alcohol consumption and negative alcohol-related consequences

Abstract: BackgroundThe aim of this study was to examine differences in alcohol consumption and its consequences when consumed alone and when mixed with energy drinks.MethodsA survey was conducted among Dutch students at Utrecht University and the College of Utrecht. We collected data on alcohol consumption and alcohol-related consequences of alcohol consumed alone and/or alcohol mixed with energy drinks (AMED). The data were analyzed using a retrospective within-subject design, comparing occasions when subjects consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…The biggest advantage of using a within-subjects design is that the same subjects are examined on different occasions, so the study results are not influenced or biased by pre-existing differences between subjects or groups, such as personality characteristics and the level of risk-taking behavior. Recent studies that have adopted this within-subjects design have found no significant or meaningful increases in overall alcohol consumption and its negative consequences when alcohol was mixed with an energy drink 812. Hence, the presumed negative effects of energy drinks found with between-groups comparisons may not be the result of whether people mix alcohol with an energy drink or not, but the results rather reflect other pre-existing differences between the groups (for example personality differences).…”
Section: Introductionmentioning
confidence: 97%
“…The biggest advantage of using a within-subjects design is that the same subjects are examined on different occasions, so the study results are not influenced or biased by pre-existing differences between subjects or groups, such as personality characteristics and the level of risk-taking behavior. Recent studies that have adopted this within-subjects design have found no significant or meaningful increases in overall alcohol consumption and its negative consequences when alcohol was mixed with an energy drink 812. Hence, the presumed negative effects of energy drinks found with between-groups comparisons may not be the result of whether people mix alcohol with an energy drink or not, but the results rather reflect other pre-existing differences between the groups (for example personality differences).…”
Section: Introductionmentioning
confidence: 97%
“…There is some evidence that energy drink co-consumption is associated increased alcohol intake (O’Brien et al, 2008, O’Brien et al, 2013, Thombs et al, 2010), although this has not been consistently demonstrated (Verster et al, 2012, de Haan et al, 2012). An additional concern is that co-consumption has been associated with an increased risk for dangerous behavior such as driving under the influence (Thombs et al, 2010), unwanted sexual encounters (O’Brien et al, 2013) and aggression (Jones et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An additional concern is that co-consumption has been associated with an increased risk for dangerous behavior such as driving under the influence (Thombs et al, 2010), unwanted sexual encounters (O’Brien et al, 2013) and aggression (Jones et al, 2012). The notion that caffeinated alcohol consumption is more hazardous has been contested, however, arguing that the likely higher incidence of co-consumption among sensation-seeking persons muddies the relationship (de Haan et al, 2012). Contradictory evidence recently showed, however, that co-consumption was associated with higher odds of hazardous behavior; even after controlling for sensation seeking tendency and the amount of alcohol consumed (O’Brien et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Such designs may be particularly beneficial in studying CAB use given recent evidence demonstrating substantial intraindividual variability in CAB use and associated consequences among users (Lau-Barraco, Milletich, & Linden, 2014; Mallett, Marzell, Scaglione, Hultgren, & Turrisi, 2014). In addition, because of the limitations of between-subject designs, such methodology has been called into question when studying the effects of CABs (de Haan, de Haan, der, Palen, Olivier, & Verster, 2012). That is, some researchers suggest that the link between CAB use and negative outcomes is better explained by one’s impulsivity or propensity toward engaging in risky behaviors in general.…”
mentioning
confidence: 99%